Etiquette Lesson for English Program in Indonesia and in China - Yohana Ika Harnita Sari; Wang Zhaohui (Master Program in Linguistics, Diponegoro University, 2020)
Life and career skills are two of many required skills in the 21st century learning. Etiquette lesson becomes essential in preparing college students to cope with the working world. This study aims at comparing the etiquette lesson employed in the English Program of the Vocational College of Universitas Gadjah Mada (UGM) Indonesia and in the Business English Program of the Foreign Language School of Chengdu Textile College (CDTC) China. The data were collected through doing interviews with etiquette teachers, doing observation in both colleges, and conducting library research. Afterwards, the data were categorized into three areas; course syllabus, topics and activities, and assessment; they were then analyzed using Business Etiquette Significant Learning Taxonomy and 21st Century Learning Framework. This study reveals that all aspects of Business Etiquette Significant Learning are employed within the lesson in both colleges.